2015
DOI: 10.1002/jsfa.7147
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the in vitro α‐glucosidase inhibitory activity of green tea polyphenols and different tea types

Abstract: Green TPs, green tea, black tea and oolong tea are excellent α-glucosidase inhibitors and their inhibitory potency is mainly attributed to TPs. These findings suggest that green tea, black tea and oolong tea can potentially be used to control postprandial hyperglycemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
3
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(40 citation statements)
references
References 22 publications
3
32
3
2
Order By: Relevance
“…IC 50 values of green tea and black tea against a-glucosidase were reported as 2.82 and 2.25 lg/mL (Yang & Kong, 2016), which were much lower than the values determined in this study. Phenolic extractions from thirty-three cultivars of blueberry showed a-glucosidase inhibition but with no IC 50 values provided (Wang, Camp, & Ehlenfeldt, 2012).…”
Section: Digestive Enzyme Inhibited By Crude and Semi-purified Extraccontrasting
confidence: 76%
“…IC 50 values of green tea and black tea against a-glucosidase were reported as 2.82 and 2.25 lg/mL (Yang & Kong, 2016), which were much lower than the values determined in this study. Phenolic extractions from thirty-three cultivars of blueberry showed a-glucosidase inhibition but with no IC 50 values provided (Wang, Camp, & Ehlenfeldt, 2012).…”
Section: Digestive Enzyme Inhibited By Crude and Semi-purified Extraccontrasting
confidence: 76%
“…He et al reported that different molecular levels of TB (≤3.5, 3.5–25, 25–50, 50–100 and ≥ 100 kDa) had an effect on hypoglycemia, particularly 25–50 kDa TB, which was 1.9 times as active as acarbose. In addition, tea polysaccharides, tea polyphenols and theaflavins had an inhibitory effect on α ‐glucosidase activity.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we selected acarbose as a positive reference drug in this study. The α-glucosidase inhibitory activity assay is commonly used for rapid in vitro screening of potential antidiabetes drugs [19,20,23].…”
Section: Discussionmentioning
confidence: 99%